PENGUNCI DINDING BATA RINGAN DENGAN BAJA TULANGAN POLOS - Muhammad Andika Ghifary; Pratikto; Anni Susilowati (Jurnal Ilmiah Teknologi Infomasi Terapan, 2023)
Most of the Indonesian regions are earthquake-prone areas. Therefore, innovation or development in building materials is needed to reduce the collapse that may occur due to earthquakes. One of them is the development of materials in building walls. From these innovations and developments in wall construction materials, research on material development was created by adding reinforcement to the walls. One of the researches is about interlocking bricks. Research was conducted on the use of reinforcement steel as pins or fasteners in interlocking wall bricks. The purpose of this research is to determine the optimum pin size for lightweight bricks and to analyze the effect of shear strength on interlocking lightweight brick walls in accordance with the provisions of SNI 8640:2018. The use of reinforcement steel as pins for interlocking lightweight brick walls involves 5 variations: not using reinforcement, using Ø8 mm reinforcement with a penetration depth of 4 cm, using Ø10 mm reinforcement with a penetration depth of 4 cm, using Ø8 mm reinforcement with a penetration depth of 3 cm, and using Ø10 mm reinforcement with a penetration depth of 3 cm. The shear strength value when using reinforcement steel in lightweight bricks tends to increase compared to lightweight bricks without reinforcement. The optimal use of reinforcement steel is with a size variation of Ø10 mm and a penetration depth of 3 cm in lightweight bricks, as it has the highest shear strength value of 1.26 MPa.